The Influence of Conventional Learning Methods on Students' Understanding of Commendable Behavior Material in Students at Elementary School 098021 Kampung Prapat - Suyanti; Manurung, Eliana Saprida; Nurhayati, Siti; Ramadhani, Riyo; Iziati (MANDAILING GLOBAL EDUKASIA, 2024)
This article aims to examine the effect of conventional learning methods on students' understanding of commendable behavior material in grade III students of SD Negeri 098021 Kampung Prapat. This study adopted a quantitative approach with an experimental design involving measuring the level of students' understanding before and after the application of conventional learning methods. In this study, conventional methods were applied through lectures, discussions, and practice questions focused on commendable behavior material that includes moral values ​​that are important to students. The data obtained were analyzed by comparing the results of the understanding test before and after the implementation of learning. The results showed that the application of conventional learning methods had a significant effect on increasing students' understanding of commendable behavior. This can be seen from the increase in the average value of student learning outcomes after they participated in conventional learning. This study highlights the importance of using appropriate learning methods in elementary education, especially in teaching moral values ​​to students. These findings contribute to the development of more effective and applicable learning strategies, as well as providing insight for educators to choose the most appropriate method in improving students' understanding of moral material taught in elementary schools.